APLIKASI KONSEP AKUNTANSI MANAJEMEN DALAM BLUE OCEAN STRATEGY - Ria Sandra Alimbudiono (Akuntansi dan Teknologi Informasi, 2008)
This article aims to describe the application of management accounting in the blue ocean strategy. Blue ocean strategy is an alternative way for success. It offers a new approach that companies have to create value innovation to satisfy customers. It does not compete in cost efficiency, but it tries to open a new demand by seeing the customer's potential needs. To implement this new approach, management needs appropriate information for making decision. Management accounting tools like target costing and life-cycle costing tries to provide information for a better quality of decision making in the blue ocean strategy. Target costing will serve information for new product's pricing and functionality and life-cycle costing tries to analyze profitability of new product during its life-cycle. By using this tools, the blue ocean strategy can be implemented in the right track.